SOBRECARGA DOMÉSTICA E TRANSTORNOS MENTAIS COMUNS EM MULHERES - Pinho, Paloma de Sousa (2006)
Introduction: The Common Mental Disorders (CMD) occur more frequently in the women and the lack of gratuity and visibility in the accomplishment of the domestic work constitutes determinative picture for the psychic disorders. Objective: To evaluate connection between domestic overload and occurrence of Common Mental Disorders in women from Feira de Santana - BA. To describe the sociodemographic characteristics, conditions of life, professional work and of the domestic work of the women. According to esteem the prevalence of the Common Mental Disorders between the women domestic overload associate to the sociodemographic aspects, conditions of life and professional work. Methodology: Epidemiologist study of transversal cut using 2057 women with age of 15 years old or more, selected through random sampling for conglomerate. The pointer of domestic overload was created from the domestic activities: washing up, pressing clothes, cleaning and cooking, weighed for the number of domicile inhabitants. The CMD had been evaluated through the SRQ-20 with cut point validated in 7 or more positive answers. Results: Between the studied women, 39.4% had presented CMD. The multiple logistic regression analysis disclosed that the women displayed to the high domestic overload had presented greater prevalence of common mental disorders (PR: 1,23; RI95%: 1,05-1,44) that the women in situations of low or average domestic overload, exactly adjusted for the variable income, schooling and leisure activities. Conclusion: The findings foment the quarrel about cultural questions and implementation of public politics for creation of a social support net to the women.